Parenting stress, social support, self-compassion, and parenting practices among mothers of children with ASD and ADHD - Riany, Yulina Eva; Ihsana, Ayu (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Parenting of children with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) faces many challenges and often causes stress amongst parents. This study aims sto analyze the differences in parenting stress, perceptions of social support, self-compassion, and parenting practices in groups of mothers of ASD children and of ADHD children. The Parental Stress Scale, the Multidimensional Scale of Perceived Social Support, the Self-compassion Scale, and the Parent Construct were used to collect the study data. The survey was taken voluntarily online by 34 mothers of ASD children (52%) and 31 mothers of ADHD children (48%). MANOVA and regression analysis were performed to test the study hypothesis. The results show that there was no significant difference in parenting stress (F=0.04, p>.05), social support (F=0.16 – 0.31, p>.05), self-compassion (F=0.01 – 1.46, p>.05), and parenting practices (F=0.04 – 2.29, p>.05) between the two groups. Parenting stress had a significant negative effect on parenting practices in both groups studied (p<.05). The study provides an overview of the parenting practices of parents of ASD and ADHD children in Indonesia.